1988
DOI: 10.1007/bf01460749
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on fluidized bed thermal storage

Abstract: Abstract. In the present work, the numerical model developed earlier by the same authors [5] is refined and recast in non-dimensional form. The refined model is calibrated with recent experiments at different bed air-inlet temperatures. Excellent agreement between the numerical results and experiments is obtained.The refined model is then used to conduct an extensive parametric study. The objectives of the parametric study are: (i) to determine the effect of the non-dimensional parameters (0(2, C( 3 and 0(,) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The application of fluidized beds to sensible heat storage has been experimentally investigated, and it has been shown that a fluidized bed behaves similar to a well-mixed tank with negligible variations in the temperature along the bed (Elsayed et al, 1988;El-Refaee et al, 1988;Megahed et al, 1988;Izquierdo-Barrientos et al, 2013Mahfoudi et al, 2015). For this reason, when the bed is coupled with a solar collector, packed beds are preferred because stratification permits an increase in the thermal efficiency of the solar collection system, as was explained in Section 2.1. and observed a heat transfer coefficient between 500 and 900 W/(m 2 K) for fluidization velocities up to 1.6 u mf .…”
Section: Fluidized Bedsmentioning
confidence: 99%
“…The application of fluidized beds to sensible heat storage has been experimentally investigated, and it has been shown that a fluidized bed behaves similar to a well-mixed tank with negligible variations in the temperature along the bed (Elsayed et al, 1988;El-Refaee et al, 1988;Megahed et al, 1988;Izquierdo-Barrientos et al, 2013Mahfoudi et al, 2015). For this reason, when the bed is coupled with a solar collector, packed beds are preferred because stratification permits an increase in the thermal efficiency of the solar collection system, as was explained in Section 2.1. and observed a heat transfer coefficient between 500 and 900 W/(m 2 K) for fluidization velocities up to 1.6 u mf .…”
Section: Fluidized Bedsmentioning
confidence: 99%